(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2017)
Previous work by the authors develops a novel technology for counter-current contacting of immiscible fluid phases based on a rotating spiral channel. The work has established theoretical modelling allowing prediction of mass transfer rates for physical absorption and desorption of dilute solute species and has verified the main hydrodynamic elements of the theory, with experimental measurements over a wide range of flow rates and liquid viscosity. A key feature of rotating spiral contacting is that the relative thicknesses of the phase layers is constant throughout the contacting process and, along with the relative phase flow rates, can be varied regardless of phase and solute properties to produce optimum conditions for the contacting. It has been shown that there are two criteria that determine the optimum. First, the flow rate ratio of the phases is matched to the equilibrium distribution of the solute between the two phases, so that sufficient solvent phase flows to allow full removal of solute from the processed stream. Second, the relative layer thicknesses should maximise specific throughput, i.e. the flow rate of the processed stream per device volume. These ideas of optimum contacting guide a comparison here of recent mass transfer data for the spiral with corresponding literature data for the packed column and rotating packed bed.